How do social contexts support practitioners’ uptake of Motivational Interviewing?: Social identification and appraisal among child and family social workers - Renko, Elina; Heino, Matti T. J.; Moilanen, Johanna; Isokuortti, Nanne; Kohonen, Katarina; Jäppinen, Maija; Hankonen, Nelli (Humanities and Social Sciences Communications, 2025)
Motivational Interviewing (MI) can improve the quality of practice of social and health professionals, but achieving sustainable change in MI skills is difficult. MI learning is often conceptualised as an individual endeavour. Social processes have been used to support MI training outcomes to some extent, but broader social contexts remain understudied. This paper focuses on the uptake of MI in child and family social work - a field that is associated with multiple social contexts (e.g., clients, colleagues, managers, teams, and multi-professional networks). It explores the different functions that social contexts play for child and family social workers in the process of taking up MI. Child and family social workers participated in an evidence-based MI training and were interviewed individually (N = 32) post-training. Content analysis was used to explore how participants described social dimensions of taking up MI. Of the various social dimensions, social appraisal and social identification (e.g., norms, modelling, social feedback, we-intentions, common agenda and collective responsibility) were highlighted as central to the MI behaviour change process. Co-workers, peer groups and managers were identified as important social groups that facilitated or hindered the uptake of MI. The importance of the MI-trained colleagues was highlighted as a key element in facilitating the uptake and maintenance of MI. Our findings highlight, in particular, the role of social planning and collective agency in MI learning. We outline recommendations for incorporating ‘the social’ into future research and practice in MI training. Social contexts hold promise for improvement and should be harnessed to support better interactional practices among health and social care professionals.